2023
DOI: 10.1039/d2ce01282k
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the non-covalent interactions in the solid state structures of dinuclear cobalt(ii) complexes with N,O-donor ligands: application of the complexes in the fabrication of Schottky devices

Abstract: Two new dinuclear cobalt(II) complexes, [(H2O)CoIIL1(μ-O2CR1)CoII(NCS)] (1) and [(DMSO)CoIIL2(μ-O2CR2)CoII(NCS)] (2) {H2L1= (2,2-dimethyl-1,3-propanediyl)bis(iminomethylene)bis(6-methoxyphenol); H2L2= (2,2-dimethyl-1,3-propanediyl)bis(iminomethylene)bis(6-ethoxyphenol); R1CO2H= 3-methyl-4-nitrobenzoic acid; R2CO2H= 4-methyl-3-nitrobenzoic acid} have been synthesized using multidentate N, O-donor ligands having two...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
1
2
0
Order By: Relevance
“…The complexes behave as monomers in solution at 23 °C, as indicated by the solution state Evans method magnetic moment measurements, and 19 F NMR in CD 3 CN shows that the triflate anion dissociates in solution (see SI). The vanadium­(V/IV) redox event for V-Na, V-K, and V-Ba is reversible and shifts anodically with an increase in the cation charge, consistent with the effect on other heterobimetallic complexes in this ligand framework. , , Computational studies were also performed, and the same trend is observed, though the simple model used in the calculations overestimates the increase in E 1/2 as the cation charge increases (see SI for computational details and Table S3 for values). The vanadium­(V/IV) reduction potential for the monocations (V-Na and V-K) shifts 90–130 mV more positive than (salen)­V­(O) and 114–164 mV more positive than (salen-OMe)­V­(O).…”
Section: Resultssupporting
confidence: 56%
“…The complexes behave as monomers in solution at 23 °C, as indicated by the solution state Evans method magnetic moment measurements, and 19 F NMR in CD 3 CN shows that the triflate anion dissociates in solution (see SI). The vanadium­(V/IV) redox event for V-Na, V-K, and V-Ba is reversible and shifts anodically with an increase in the cation charge, consistent with the effect on other heterobimetallic complexes in this ligand framework. , , Computational studies were also performed, and the same trend is observed, though the simple model used in the calculations overestimates the increase in E 1/2 as the cation charge increases (see SI for computational details and Table S3 for values). The vanadium­(V/IV) reduction potential for the monocations (V-Na and V-K) shifts 90–130 mV more positive than (salen)­V­(O) and 114–164 mV more positive than (salen-OMe)­V­(O).…”
Section: Resultssupporting
confidence: 56%
“…It was believed that the quality of the metal-semiconductor interface and the surface conditions had a substantial impact on the characteristics of devices. 90 A comparison of the electrical parameters of the complexes with some other cobalt complexes 58,64,98–100 reported in the literature is given in Table 5, which shows that the barrier height of complex 1 is minimum among all three complexes. Only two other cobalt complexes [(N 3 ) 2 CoL 5 Na(DMF)] and [(DMSO)Co II L 4 (μ-O 2 CR 2 )Co II (NCS)] are reported in the literature, whose barrier heights are less than that of complex 1 .…”
Section: Resultsmentioning
confidence: 98%
“…Thus, the limited range of the positive voltage axis does not negate the overall exponential nature of the diode's behavior. The comparison of electrical parameters of our synthesized complex with some other cobalt complexes 17,40,58,59 reported in literature is given in Table 7. It demonstrates that our synthesized complex exhibits photosensitivity whereas the other reported complexes do not.…”
Section: Electrical Characterizationmentioning
confidence: 99%